Digital Information Literacy as A Foundation for E-Learning: A Study of Higher Education in West Nusa Tenggara - Nurlita Lestariani; Neneng Agustiningsih; Ilham Handika (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2025)
This study contributes to the understanding of how digital information literacy (DIL) supports e-learning implementation in under-resourced higher education contexts. This study used a quatitative approach and ex post facto research. Data analysis in this study used descriptive methods (quantitative). The subjects of this study were 56 lecturers and 300 students of Biology Education programs from various universities in West Nusa Tenggara. Data were collected using questionnaires (sig. 0.00-0.04 and Cronbach Alpha=0.743) and documentation. The results of the study indicate that the level of implementation of DIL in universities in NTB has been moderately high, through three process: planning, implementation, and evaluation of learning. The majority of lecturers in NTB (82%) have a high level of DIL, with significant advantages in the aspects of understanding the purpose and meaning of information and the ability to evaluate information. On the other hand, students also have a fairly high level of DIL (68%), but the rest are still at moderate and low levels. Strengthening DIL, especially for students, still needs better attention, through optimal support from lecturers and universities. By improving overall digital information literacy, universities in NTB can be more prepared and effective in facing the challenges of digitalization of education in the Society 5.0 era.